2008
DOI: 10.1007/s00702-007-0844-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of polymorphisms throughout GAD1 gene: a family-based association study in schizophrenia

Abstract: Studies suggest that GAD1 gene is a functional candidate susceptibility gene for schizophrenia. In order to investigate the contribution of GAD1 gene to the etiology of schizophrenia in Chinese, we carried out a family-based association study between GAD1 gene and schizophrenia in 235 Chinese Han family trios. The GAD1 gene is comprehensively analyzed using a systematic mutation scan and the following-up association studies between common SNPs and schizophrenia in both single-locus and haplotype levels. Altoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Most schizophrenia studies focus on adults, but the pathogenesis probably involves early brain development (Marenco and Weinberger, 2000). Genetic variation in GAD1, the gene for the GABA synthetic enzyme GAD67, may be an etiologic factor in schizophrenia (Addington et al, 2005;Straub et al, 2007;Du et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most schizophrenia studies focus on adults, but the pathogenesis probably involves early brain development (Marenco and Weinberger, 2000). Genetic variation in GAD1, the gene for the GABA synthetic enzyme GAD67, may be an etiologic factor in schizophrenia (Addington et al, 2005;Straub et al, 2007;Du et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A great many of evidences indicated that GAD1 played more and more important role in nerve system disease such as autism and schizophrenia. Many studies on the association between GAD1 and nerve system diseases have been conducted and their results proved that the abruption of GAD1 gene was an important risk factor to the happening of schizophrenia, autism and child bipolar I disorder [11][12][13][14]. There was also a study which demonstrated that GAD1 was associated with cortical gray matter volume loss in schizophrenia [15].…”
mentioning
confidence: 90%
“…Several studies of the gene that encodes GAD67, GAD1, have yielded a number of single-nucleotide polymorphisms that are found more frequently in schizophrenic patients than controls [36,37,38]. The majority of single-nucleotide polymorphisms in each study was found in gene regulatory sequences suggesting a role in regulating gene expression and not protein function.…”
Section: Gaba-associated Deficits In Schizophreniamentioning
confidence: 99%